PENERAPAN CASE BASED LEARNING UNTUK MENINGKATKAN HIGHER ORDER THINKING SKILLS (HOTS) SISWA DI SMAN 4 PARIAMAN - Abdul Razak; Nofrion (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of applying Case Based Learning to improve Higher Order Thinking Skills (HOTS) of SMAN 4 Pariaman students. This research uses the Quasy Experiment method with a quantitative approach and this research design uses Pre-test - Post-test Control Group Design. The study population was class X students in the 2024/2025 academic year with a total of 244 students from 7 classes. The research sample consisted of class X.E3 as the control class and class X.E1 as the experimental class selected using purposive sampling technique. Data collection techniques include observation, documentation, and tests. The results showed the average Pre-test of the experimental class was 54.87 and Post-test was 83.53, while the control class obtained Pre-test 58.65 and Post-test 76.93. There was a significant increase in the experimental class. The Paired Sample T-Test test results show a significance level (sig) of 0.001. Because this significance value is smaller than 0.05, Ho is rejected and Ha is accepted.